A long-term record of the physiological plasticity of stomatal condactance in Proteaceae - Cronin, Kate (Department of Biological Sciences, 2015)
Bioclimatic models suggest that Protea species are likely to be severely affected by predicted increases in temperature and reductions in rainfall in the Western Cape. However, throughout their 400 million year history, land plants have been exposed to considerable climatic variations that have driven physiological adaptations promoting long-term resilience. A principal response of plants to increases in atmospheric CO2 concentration and changing rainfall regimes is to minimise water loss by reducing stomatal conductance (gs) and simultaneously increasing intrinsic water-use efficiency (iWUE). Plasticity in these two physiological traits may enhance the ability of plants to survive future climate change. There is considerable evidence in the literature for major changes in gs and iWUE in response to both short-term and long-term changes in environmental conditions. However, to date, the effects of decadal climate change on plant physiology are still largely uncertain. In this study, the responses of gs and iWUE to perturbations in rainfall and atmospheric CO2 are reconstructed from a chronological sequence of herbarium and modern Protea specimens. The results indicate that in the two high-altitude study species, P.cryophila (t= -2.44, df=7, p= 0.045) and P.venusta (t=3.08, df=5, p=0.027), stomatal conductance has significantly declined in response to increasing atmospheric CO2 concentrations over the past century. The low altitude species appears to maintain fixed stomatal conductance trajectories as a response to more xeric conditions. It is difficult to draw inferences about stomatal physiological plasticity from iWUE data as it is not possible to distinguish between the effects of physiological reductions in stomatal conductance and biochemical enhancement of photosynthesis. Microhabitat sensitivity in iWUE is a further factor confounding interpretation. This highlights the importance of using multiple parameters as analytical tools for assessing long-term physiological change. A key contribution of this study is that it has confirmed the value of using archival material and highlights methodologies that may aid future herbarium-based interpretations. In addition, despite some methodological limitations, the study has identified interesting trends at climate change-relevant timescales that point the way for further research to understand relative vulnerabilities and inform conservation strategies. Specifically, it suggests that future research and conservation efforts may need to be focused on species occurring at low altitudes because of their apparently more limited physiological plasticity.